A New Numerical Procedure for Determination of Effective Elastic Constants in Unidirectional Composite Plates - Daryazadeh, S.; Lvov, Gennadiy I.; Tajdari, M. (Islamic Azad University, 2016)
In this paper a composite plate with similar unidirectional fibers is considered. Assuming orthotropic structure, theory of elasticity is used for investigating the stress concentration. Also, complex variable functions are utilized for solving the plane stress problems. Then the effective characteristics of this plate are studied numerically by using ANSYS software. In this research a volume element of fibers in square array is considered. In order to investigate the numerical finite element modeling, the modeling of a quarter unit cell is considered. For determining the elasticity coefficients, stress analysis is performed for considered volume with noting to boundary conditions. Effective elasticity and mechanical properties of composite which polymer epoxy is considered as its matrix, are determined theoretically and also by the proposed method in this paper with finite element method. Finally, the variations of mechanical properties with respect to fiber-volume fraction are studied.
Keywords: composite plate; unidirectional fibers; effective elastic constants; orthotropic plate